(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: It has been shown that the chronic metabolic derangement accompanying long standing hyperglycemia, both in experimentalanimals and man, may alter fertility in males. This work investigate the role of lisnopril in improving fertility parameters .Aim of the study: To evaluate the role of lisnopril with respect to fertility parameters in experimentally induced hyperglycemia in rats.Materials and methods: Three groups of rats were subjected to alloxan induced hyperglycemia, placebo treatment (control group), andalloxan and lisnopril treatment (study group). Each group included 10 animals. Sperm parameters, hormonal levels, markers of oxidativestress and histophotometry were done .Results: Sperm parameters in the form of sperm count, normal morphology, motility and number of dead sperms were significantly alteredfollowing alloxan induced hyperglycemia (P < 0.001). The administration of lisnopril showed significant improvement in sperm parameters(P <0.001) in addition to significant improvement in markers of oxidative stress, GSH, SOD, MDA and NO (P < 0.001), and in hormonallevels, testosterone and FSH (P < 0.001).Conclusion: Lisnopril is useful in optimizing fertility parameters in experimental rats following alloxan induced hyperglycemia throughantioxidant mechanisms and improved hormonal profile.